2015
DOI: 10.12968/bjmh.2015.4.3.122
|View full text |Cite
|
Sign up to set email alerts
|

The experience of PTSD following childbirth

Abstract: Post traumatic stress disorder (PTSD) is a significant mental health problem which can develop following childbirth (PTSD FC). Partners and staff are also at risk and a larger group of women develop sub-clinical trauma symptoms. PTSD can impact on future childbearing, the wider family, intimate sexual relationships and bonding. The relationship between mothers and health professionals is crucial. Health professionals can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…For example, while some cultures promote special foods and rest for pregnant women, in other societies pregnant women are expected to continue working routinely. In addition, nutritional taboos may deprive pregnant women of essential nutrients particularly iron, protein, vitamin B 12 and folic acid 19 . Mgata and Maluka in their study in Dar es Salaam reported that perceptions of antenatal care, past experience with pregnancy, fear of pregnancy disclosure, socio-cultural beliefs, age, occupation, marital status, parity, behaviour and knowledge level were key individual and social factors for late ANC attendance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while some cultures promote special foods and rest for pregnant women, in other societies pregnant women are expected to continue working routinely. In addition, nutritional taboos may deprive pregnant women of essential nutrients particularly iron, protein, vitamin B 12 and folic acid 19 . Mgata and Maluka in their study in Dar es Salaam reported that perceptions of antenatal care, past experience with pregnancy, fear of pregnancy disclosure, socio-cultural beliefs, age, occupation, marital status, parity, behaviour and knowledge level were key individual and social factors for late ANC attendance.…”
Section: Introductionmentioning
confidence: 99%
“…Women are often dissatisfied with intrapartum care because their needs and expectations are not met (Kifle et al, 2017). Moreover, in a recent review, Bohren et al (2019a) reported that women's negative perceptions of birth persisted over a long period of time and increased the likelihood of adverse maternal outcomes, such as postpartum depression and fear of subsequent birth (Garthus-Niegel et al, 2013;Poote & McKenzie-McHarg, 2015). Vedam et al (2019) highlighted the frequent mistreatment of women during childbirth in hospital settings in the United States, which was often related to unexpected medical interventions.…”
mentioning
confidence: 99%